Analisis Kualitas Air Tanah Dangkal untuk Keperluan Air Minum Di Kota Cimahi - Eka Wardhani; Luvina Oktavia Lukman Putri (Jurnal Serambi Engineering, 2021)
Groundwater is the  primary source of clean water for  Cimahi City residents. Groundwater quality has decreased due to contamination of domestic wastewater as it is managed  through  local systems that do not meet standards. This study aims to analyse  the feasibility of shallow groundwater as a source of clean water in the town of Cimahi . The data used are  secondary to the Environment Service for  2018. Sampling was conducted  in 12 urban villages such as Citeureup, Pasir Kaliki, Cibeureum, Cibabat, Cipageran, Cimahi, Leuwigajah, Setiamanah, Cibeber, Baros, Karang Mekar, and Melong. There are 1 to 2 samples in  each village  . Based on field measurements, several parameters have not  exceeded the required quality standards, namely turbidity, Manganese, Nitrate, MBAS Detergent, and Total Coliform. Groundwater quality from 20 sampling points only 4 points (20%) which  meet the quality standards and are suitable as a water source, the remaining 16 sampling points (80%) are declared unfit for sampling because  one to three parameters that do not meet the quality standards. Management can occur by improving the local system or by beginning  to plan a centralized wastewater treatment system that uses piping to reduce  groundwater contamination.